How Precise Is Dental Volumetric Tomography in the Prediction of Bone Density? - Hakan Bilhan; Selda Arat; Onur Geckili (International Journal of Dentistry)
Objectives. The aim of this study was to review the bone density assessment techniques and evaluate the macroscopic structure of bone specimens scored by Hounsfield Units (HUs) and decide if they are always in congruence. Methods. The mandible of a formalin-fixed human cadaver was scanned by dental volumetric tomography (DVT) for planning of the specimen positions and fabrication of a surgical guide and a surgical stent was fabricated afterwards. Bone cylinders of 3.5 mm diameter and 5 mm length, were excised from the mandible using the surgical stent with a slow speed trephine drill. After removal of the cylinders two more scans were performed and the images of the first scan were used for the determination of the HU values. The removed bone cylinder was inspected macroscopically as well by micro-CT scan. Results. The highest HU values were recorded in the interforaminal region, especially in the midline (408–742). Posterior regions showed lower HU values, especially the first molar regions (22–61 for the right; 14–66 for the left first molar regions). Conclusion. Within the limitations of this pilot study, it can be concluded that HU values alone could be a misleading diagnostic tool for the determination of bone density.